Creation of Mo/Tc@C60 and Au@C60 and molecular-dynamics simulations. Issue 32 (1st June 2021) - Ohtsuki, Tsutomu; Manjanath, Aaditya; Ohno, Kaoru; Inagaki, Makoto; Sekimoto, Shun; Kawazoe, Yoshiyuki
Abstract : The formation of Mo, Au-incorporated fullerenes was investigated using radionuclides produced by nuclear reactions and using AIMD simulations. The possibility of the formation of endohedral fullerenes containing Mo/Tc and Au atoms is verified. Abstract : The formation of middle- and/or high-weight atom (Mo, Au)-incorporated fullerenes was investigated using radionuclides produced by nuclear reactions. From the trace radioactivities of 99 Mo/ 99m Tc or 194 Au after high-performance liquid chromatography, it was found that the formation of endohedral and/or heterofullerene fullerenes in 99 Mo/ 99m Tc and 194 Au atoms could occur by a recoil process following the nuclear reactions. Furthermore, the 99m Tc (and 194 Au) atoms recoiled against β-decay remained present inside these cages. To confirm the produced materials experimentally, ab initio molecular dynamics (MD) simulations based on an all-electron mixed-basis approach were performed. The possibility of the formation of endohedral fullerenes containing Mo/Tc and Au atoms is verified; here, the formation of heterofullerenes is excluded by MD simulations. These findings suggest that radionuclides stably encapsulated by fullerenes could potentially play a valuable role in diagnostic nuclear medicine.